Urban development and transport disadvantage: Methodology to evaluate social transport needs in Latin American cities - Carmen Lizarraga; Ciro Jaramillo; Alejandro L. Grindlay (European Regional Science Association (ERSA), 2011)
This article examines the theoretical framework for accessibility, social exclusion and provision of public transport. The socio-economic and urban characteristics of Latin American cities require the creation of specific indices to determine social needs for public transport. In the article an index of social transport needs is drawn up. It can be used to highlight a problem which is severely affecting wide groups in Latin America who suffer social exclusion aggravated by a deficient provision of public transport, and that the planning of public transport systems must take into account mechanisms which include social needs in the decision making process.
Keywords: 330